Cation‐Directed Dimeric versus Tetrameric Assemblies of Lanthanide‐Stabilized Dilacunary Keggin Tungstogermanates. Issue 38 (5th August 2014) - Artetxe, Beñat; Reinoso, Santiago; San Felices, Leire; Lezama, Luis; Gutiérrez‐Zorrilla, Juan M.; García, José A.; Galán‐Mascarós, José Ramón; Haider, Ali; Kortz, Ulrich; Vicent, Cristian
Abstract Reaction of mid‐ to late lanthanide ions with GeO2 and Na2WO4 in NaOAc buffer results in a library of [Ln2(GeW10O38)]6− clusters (Ln2), which consist of dilacunary Keggin fragments stabilized by the insertion of 4f atoms in the vacant sites and show the ability to undergo cation‐directed self‐assembly processes. In the presence of Na+, two β‐Ln2 subunits assemble by means of Ln‐O(WO5)‐Ln bridges to form the chiral [Ln4(H2O)6(β‐GeW10O38)2]12− dimeric anions (ββ‐Ln4, Ln=Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu). When Cs+ is present, two Ln4‐like dimers further assemble into the [Ln4(H2O)5(GeW10O38)22]24− species (Ln8, Ln=Ho, Er, Tm, Yb, Lu). Two types of tetramers coexist in the solid state: One shows a full ββ‐Ln8 architecture, whereas the other one is a mixed αβ‐Ln8 assembly in which each β‐subunit is linked to its corresponding α‐Ln2 derivative. Regardless of differences in isomeric forms and the relative arrangement of Ln2 subunits, all anions display virtually identical Ln4 cores as a common structural feature. A combination of ESI mass spectrometry and 183W NMR spectroscopy experiments indicates that Ln8 tetramers fragment into Ln4 dimers upon dissolution, which undergo partial dissociation into Ln2 monomers and slow dimer/monomer equilibration. This is most likely followed by β‐to‐α isomerization of Ln2 clusters with consequent reassembly, as indicated by isolation of three additional αα‐Ln4 derivatives. Magnetic and photoluminescence properties in the Na‐ββ‐Ln4 series are also discussed.